Internal consistency, construct validity, and responsiveness of the MRC Prion Disease Rating Scale - Leah Leidy; Aaron Yarlas; Robert S. Pulido; Jessica Ludwig; Kathleen Glisic; Brian S. Appleby (Journal of Patient-Reported Outcomes)
Abstract Background The Medical Research Council-Prion Disease Rating Scale (MRC-PDRS) is a 20-point clinician-reported outcome scale to assess disease progression in patients with prion disease, an invariably fatal neurodegenerative disease caused by misfolded prion protein. This study aims to evaluate the measurement properties and interpretability of the MRC-PDRS to support the measure’s use for effective disease management and research evaluating effectiveness of treatment options for prion diseases. Methodology Utilizing patient data from the Telemedicine Assessment Program for CJD (TAPCJD), statistical assessment was conducted of internal consistency, construct validity (including convergent, divergent validity, and known-groups discriminant validity), responsiveness, and interpretation guidelines using distribution-based approaches to estimate thresholds indicating minimal important change (MIC) in MRC-PDRS scores. Criterion measures used for evaluating construct validity and responsiveness included the Telephone Interview for Cognitive Status (TICS) and Neuropsychiatric Inventory–Questionnaire (NPI-Q). Results/Conclusions These findings provide strong preliminary evidence that the MRC-PDRS is reliable, valid, and responsive as a tool for measuring disease progression in patients with prion disease, with preliminary MIC estimates ranging from 1 to 3 points. This supports the use of MRC-PDRS in evaluating potential treatment benefits of prion disease clinical trials, and potentially in clinical practice settings.